2018
DOI: 10.3892/mmr.2018.8842
|View full text |Cite
|
Sign up to set email alerts
|

miR‑152 regulates TGF‑β1‑induced epithelial‑mesenchymal transition by targeting HPIP in tubular epithelial cells

Abstract: Renal fibrosis is a common pathological feature of chronic kidney diseases, and their development and progression are influenced by epigenetic modifications including aberrant microRNA (miRNA or miR) expression. miRNAs have been demonstrated to modulate the aggressiveness of various cancers and have emerged as possible therapeutic agents for the management of renal fibrosis. Transforming growth factor β1 (TGF‑β1)‑induced epithelial‑mesenchymal transition (EMT) of tubular epithelial cells serves a role in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Zhao et al (2017) found that miR-30c inhibited EMT through Snail1-TGF-β1 pathway, and attenuated diabetic nephropathy. In another study, researchers found that miR-152 overexpression inhibited TGF-β1-induced EMT in HK-2 cells (Ning et al, 2018). It is hard to identify which miRNA determines EMT initiation, and some have suggested unbalanced control of several miRNAs.…”
Section: Micrornamentioning
confidence: 99%
“…Zhao et al (2017) found that miR-30c inhibited EMT through Snail1-TGF-β1 pathway, and attenuated diabetic nephropathy. In another study, researchers found that miR-152 overexpression inhibited TGF-β1-induced EMT in HK-2 cells (Ning et al, 2018). It is hard to identify which miRNA determines EMT initiation, and some have suggested unbalanced control of several miRNAs.…”
Section: Micrornamentioning
confidence: 99%
“…This trend was confirmed by the reduced expression of miR-152-3p in B. vulgatus -A2 CFS-treated organoids from PCeD. Even if miR-152-3p has a positive effect on CeD signaling pathways in different pathological contexts, 49 , 50 to the best of our knowledge, no studies have been reported in literature that specifically correlate this miRNA to CeD. Interestingly, in our dataset miR-152-3p is the only miRNA to be significantly modulated in PCeD versus HC organoids at basal condition.…”
Section: Discussionmentioning
confidence: 68%
“…Previously, several miRNAs were reported to be associated with renal fibrosis [ 3 , 13 , 14 , 15 , 16 , 17 , 18 ]—the expression levels of miR−21, −22, −135a, −150, −155, −184, −214, −215, −216a, −324, −433, and −1207 were upregulated in fibrotic kidneys [ 18 , 29 , 30 , 31 , 32 ]. In contrast, the expression levels of let-7, miR−29, −30, −34, −152, −181, −194, −200, and −455 were downregulated in fibrotic kidneys [ 18 , 21 , 33 , 34 , 35 ]. In this study, we confirmed that the expression levels of three miRNAs (miR−511−3p, −375−3p, and −127−3p) were significantly upregulated, and the expression levels of three miRNAs (miR−122−5p, −504−3p, and −363−3p) were significantly downregulated, in fibrotic kidneys by qRT−PCR.…”
Section: Discussionmentioning
confidence: 99%